Supreme court's judicial review authority vs. constitutional supremacy in the Maldives: does the constitution still reign supreme? - Shafie, Aminath Asfa; Ab Aziz, Shamrahayu (IIUM Press, International Islamic University Malaysia, 2019)
The Supreme Court of Maldives is entrusted with the responsibility of upholding the supremacy of the Constitution. However, within the last ten years, the Supreme Court has been criticized for the Court’s slow but steady progression to encroach on the powers of the parliament and as a result, undermine the supremacy of theConstitution. The objective and purpose of this article are to entail how the Supreme Court of Maldives had utilized its power to judicial review to undermine the supremacy of the Constitution over the years. This article useslibrary-based research. Itanalysesthe principles of separation of powers, checks and balances and judicial review and how these principles are adopted in the Maldives.In addition, this article reviews and analyzes the decisions of the Supreme Court which are in contradiction to the Constitution.The findings of the article are evidential of how the Supreme Court had performed the constitutionally mandated legislative functions of the parliament through the Court’s power to judicial review. The Supreme Court had established guidelines, regulated the rights and freedoms specified in the Constitution, and determined procedures. This article concludesbyemphasizing the importance of exercising restraint when performing the constitutionally mandated functionsof each branch, in order to ensure the supremacy of the Constitution as well the effective functioning of the three branches of government.